(untitled) (Entrepreneurship Journal for Finance and Business, 2023)
This study aims to test whether the institutions listed on the Iraq Stock Exchange have a significant correlation between the level of conservative accounting practice with the level of market share returns during the Coronavirus pandemic period as one of the policies to confront the economic repercussions of the Coronavirus pandemic. Furthermore, the sample included institutions listed on the Iraq Stock Exchange during the 2019 and 2020 years, i.e., the period before the Coronavirus pandemic and during the Coronavirus pandemic for the purpose of comparison. The market value to book value model was used, and the study found that conservative institutions had achieved the highest level of market share prices compared to non-conservative institutions, and the study also found that conservative institutions during the Coronavirus pandemic had achieved a higher correlation coefficient during the pandemic compared to the pre-pandemic period, where it reached Pearson correlation coefficient (0.932) during the 2020 year for conservative institutions, while the Pearson correlation coefficient between conservatism and the market value of shares reached (0.853) during 2019,and A study found that the effect of accounting conservatism on market share prices for the year 2019 amounted to (0.731), which is significant regression, and in 2020 it reached (0.852), which is a significant regression, that is, the effect increased by (0.121) during the pandemic period , and this is evidence of the market need for conservatism. Therefore, our study recommends the adoption of accounting conservatism, but in a reasonable manner without exaggeration to face challenges and crises, because the market trusts more conservative accounting policies compared to the impulsive policy.